Sustainability in the Development of Water Systems Management - Molina, José-Luis (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The concept of sustainability has been intensively used over the last decades since Brundtland´s report was published in 1987. This concept, due to its transversal, horizontal and interdisciplinary nature, can be used in many disciplines, scenarios, spatio-temporal dimensions and different circumstances. The intensive development in recent years of analytical techniques and tools based on disciplines such as artificial intelligence, machine learning, data mining, information theory and the Internet of Things, among others, has meant we are very well-placed for analysing the sustainability of water systems in a multiperspective way. Water systems management requires the most advanced approaches and tools for rigorously addressing all the dimensions involved in the sustainability of its development. Consequently, addressing the sustainability of water systems management may comprise physical (natural processes), chemical, socioeconomic, legal, institutional, infrastructure (engineering), political and cultural aspects, among others. This Special Issue welcomes general and specific contributions that address the sustainability of water systems management considering its development. Special interest will be given to those contributions that consider tradeoffs and/or integration between some of the aspects or disciplines that drive the sustainability of water systems in the context of their management and development.